Cam Jansen : the mystery of the stolen diamonds - Adler, David A.; Natti, Susanna (New York : Puffin, 2010)
A fifth-grader with a photographic memory and her friend Eric help solve the mystery of the stolen diamonds.
Elem. School Library Collection
School Library Journal
Wilson's Children
Booklist, February 2001
Elem. School Library Collection, June 2000
School Library Journal, December 2001
Keywords: Diamonds -- Fiction; Girls -- Fiction; Jansen, Cam (Fictitious character) -- Fiction; Mystery and detective stories; Stealing -- Fiction; Diamonds -- Fiction; Girls -- Fiction; Jansen, Cam (Fictional character) -- Fiction; Mystery fiction; Theft -- Fiction